Re-assembling land degradation: toward a nature-society-inclusive soil erosion management strategy. A case of the Rwenzori region, Uganda - Tibasiima, Thaddeo Kahigwa; Bwambale, Bosco; Ekyaligonza, Deous Mary; Dietrich, Phillipp; Jumba, Francis; Kagorora, John Patrick Kanahe; Freyer, Bernard (Frontiers in Sustainable Food Systems, 2023)
Effective control of land degradation is increasingly noted to require bridging the mismatch between science, policy, and practice. This further requires not only understanding land degradation as an assemblage or hybrid of the biophysical and anthropogenic aspects; but also, an epistemology that levels the grounds between scientists, policymakers, and farmers whose farm livelihoods are at-risk. Towards this need, the recently proposed hylomorphic (disaster risk management) framework is tested. This framework structures the procedure of bridging lived experiences (of those at risk) with the theoretical knowledge (of scientists and policymakers) to enable the co-creation of knowledge and co-designing options for managing natural risks. This study is the first to test this framework in a case of soil erosion. We focused on the Rwenzori (Uganda), where soil erosion is a major form of land degradation. We aimed to test the possibility of producing a hybrid knowledge theory and strategy for sustainable soil erosion management. Drawing on insights from this study and proving this framework, we note that lived experiences expose blind spots in understanding the local context of soil erosion; additionally, flatten the ontology and facilitate a hybrid context-specific epistemology towards a more nature-society-inclusive soil erosion management strategy.